Vaccinating Against Hate: Using Attitudinal Inoculation to Confer Resistance to Persuasion by Extremist Propaganda - Braddock, Kurt (Terrorism and political violence, 2022)
Research in several domains has shown that attitudinal inoculation effectively promotes resistance to persuasion. Despite its proven efficacy, inoculation has not been empirically tested as a strategy for preventing the adoption of beliefs and attitudes consistent with violent extremist ideologies. The current study addresses this gap in the literature. In a between-subjects experiment performed in the U.S., participants (N = 357) were exposed to an inoculation message or no-inoculation control message before reading left- or right-wing extremist propaganda. Inoculation positively predicted psychological reactance, which in turn, reduced intention to support the extremist group. Inoculation also negatively predicted perceptions of the extremist group’s credibility, which positively predicted support intention. Neither the apparent source of the inoculation message, nor the ideological focus of the propaganda, moderated any of these relationships. These results effectively extend the scope of inoculation theory into the realm of violent extremism and have implications for the development of messages intended to prevent persuasive outcomes consistent with extremist ideologies.